Enzyme self-label-bound ATTO700 in single-molecule and super-resolution microscopy. Issue 99 (25th November 2022) - Trumpp, Michael; Oliveras, Anna; Gonschior, Hannes; Ast, Julia; Hodson, David J.; Knaus, Petra; Lehmann, Martin; Birol, Melissa; Broichhagen, Johannes
Abstract : Near-infrared ATTO700 is evaluated as an acceptor in SNAP- and Halo-tag protein labelling for ensemble and single molecule Förster Resonance Energy Transfer (FRET) and in stimulated emission by depletion (STED) super resolution microscopy. Abstract : Herein, we evaluate near-infrared ATTO700 as an acceptor in SNAP- and Halo-tag protein labelling for Förster Resonance Energy Transfer (FRET) by ensemble and single molecule measurements. Microscopy of cell surface proteins in live cells is perfomed including super-resolution stimulated emission by depletion (STED) nanoscopy.